(untitled) (American Journal of Language, Literacy and Learning in STEM Education (2993-2769), 2024)
This article provides a concise overview of a study exploring the lexical-semantic features of proverbs based on somatisms in both English and Uzbek languages. It highlights the cultural significance of proverbs, particularly those utilizing body part idioms, in conveying wisdom, values, and societal norms. By examining the semantic nuances and linguistic structures of these proverbs across different cultural contexts, the study offers insights into the rich tapestry of human expression and cross-cultural communication.